Stemness-Attenuating miR-503-3p as a Paracrine Factor to Regulate Growth of Cancer Stem Cells - Seo, Minkoo; Kim, Seung Min; Woo, Eun Young; Han, Ki-Cheol; Park, Eun Joo; Ko, Seongyeol; Choi, Eun Wook; Jang, Mihue (HINDAWI LTD, 2018)
Cancer stem cells (CSCs) with self-renewal abilities endorse cellular heterogeneity, resulting in metastasis and recurrence. However, there are no promising therapeutics directed against CSCs. Herein, we found that miR-503-3p inhibited tumor growth via the regulation of CSC proliferation and self-renewal. miR-503-3p, isolated from human adipose stem cell- (ASC-) derived exosomes, suppressed initiation and progression of CSCs as determined by anchorage-dependent (colony formation) and anchorage-independent (tumorsphere formation) assays. The expression of pluripotency genes was significantly decreased in miR-503-3p-treated CSCs. Furthermore, xenografts, which received miR-503-3p, exhibited remarkably reduced tumor growth in vivo. Thus, miR-503-3p may function as a stemness-attenuating factor via cell-to-cell communications.
Keywords: EXTRACELLULAR VESICLES; EMERGING ROLE; SELF-RENEWAL; EXOSOMES; PROLIFERATION; MICROVESICLES; MICRORNA; LEUKEMIA; APOPTOSIS; DELIVERY